The Ability of KUB Rooster to Produce Indonesian Super Native Chickens - Zulfan, Zulfan; Yaman, Muhammad Aman; Ariga, Muhammad Faris; Ammar, Muhammad (Faculty of Animal Science, Universitas Brawijaya, 2024)
The crossbreed originated from male native chicken x female commercial layers, currently in Indonesia called a Super Native Chicken (Ayam Kampung Super). This study aimed to evaluate the ability of a selected local KUB (Ayam Kampung Unggul Balitbangtan) rooster to cross female ISA Brown chickens to produce Indonesian super native chickens. In comparison, the ISA hen was crossed with an unselected local chicken of bangkok descent (Ayam Kampung Turunan Bangkok, KTB) rooster, and the same hen strain was crossed with a Rhode Island Red (RIR) rooster. The treatment was crossbreeding (CB): CB1= KUB x ISA, CB2= KTB x ISA, and CB3= RIR x ISA. The results of the study showed that there were no significant (P>0.05) effects on fertility, hatchability, embryonic mortality, or chick abnormalities, but KUB x ISA resulted in significantly greater (P<0.01) chick weight and chick yield than did KTB x ISA. In conclusion, the KUB rooster was able to cross with ISA Brown to produce Super Native Chicken without significant adverse effects on fertility or hatchability, resulting in better quality day-old chicks than those produced by the KTB rooster.